Deep brain stimulation can regulate arterial blood pressure in awake humans. - Green, A; Wang, S; Owen, S; Xie, K; Liu, X; Paterson, D; Stein, J; Bain, P; Aziz, T (2005)
The periaqueductal grey matter is known to play a role in cardiovascular control in animals. Cardiovascular responses to electrical stimulation of the periventricular/periaqueductal grey matter were measured in 15 awake human study participants following implantation of deep brain stimulating electrodes for treatment of chronic pain. We found that stimulation of the ventral periventricular/periaqueductal grey matter caused a mean reduction in systolic blood pressure of 14.2+/-3.6 mmHg in seven patients and stimulation of the dorsal periventricular/periaqueductal grey matter caused a mean increase of 16.7+/-5.9 mmHg in six patients. A comparison between ventral and dorsal electrodes demonstrated significant differences (P<0.05). These changes were accompanied by analogous changes in diastolic blood pressure, pulse pressure, maximum dP/dt but not in the time interval between each R wave on the electrocardiogram.